Sensorless speed control of IM pumping system fed by solar power generation. (2016) - Bouzeria, Hamza; Fetha, Cherif; Bahi, Tahar; Abadlia, Issam; Layate, Zakaria; Lekhchine, Salima
This paper presents the study of the photovoltaic pumping process driven by induction motor. The configuration of the studied conversion chain which contains the photovoltaic generator is adapted by a DC-DC converter controlled using the fuzzy logic technique. The induction motor is controlled by a variable hysteresis band, in order to ensure the continuation of the maximum power point of a three-phase inverter and two levels that supplied. The objective of this process is to ensure the operation at maximum power of the PV system under various conditions of temperature and irradiation. The matching between the PV generator and the load was also performed, with the boost converter. Technical vector control sensors of induction motor have been developed and are presented. A control law without mechanical sensor using an adaptive observer estimates the speed based on proportional integral controller. Moreover, adaptation of the rotor time constant is powered by a photovoltaic solar energy, the latter control system adopts inverter current control scheme with variable hysteresis band. Modelling and simulation study performs the proposed process. Electrical and mechanical characteristics of the propuse are simulated and tested by MATLAB/Simulink.